2014
DOI: 10.1007/s00431-014-2343-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung function of preterm infants before and after viral infections

Abstract: These results suggest viral LRTIs, regardless of whether hospitalisation is required, adversely affect prematurely born infants' airway resistance at follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…This is predominantly in the form of asthma, but viral LRTI has even been proposed as an etiology of chronic bronchitis (34), obstructive pulmonary disease (35)(36)(37), and idiopathic pulmonary fibrosis (38,39). In a retrospective study of preterm infants with viral LRTIs, significantly elevated airway resistance remained after 1 year of follow-up (40). RSV infection was the most prevalent lower respiratory tract infection that was detected among a panel of common respiratory viruses (40).…”
Section: Infection In Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is predominantly in the form of asthma, but viral LRTI has even been proposed as an etiology of chronic bronchitis (34), obstructive pulmonary disease (35)(36)(37), and idiopathic pulmonary fibrosis (38,39). In a retrospective study of preterm infants with viral LRTIs, significantly elevated airway resistance remained after 1 year of follow-up (40). RSV infection was the most prevalent lower respiratory tract infection that was detected among a panel of common respiratory viruses (40).…”
Section: Infection In Infantsmentioning
confidence: 99%
“…In a retrospective study of preterm infants with viral LRTIs, significantly elevated airway resistance remained after 1 year of follow-up (40). RSV infection was the most prevalent lower respiratory tract infection that was detected among a panel of common respiratory viruses (40). The increased resistance is most likely a product of the airway inflammation and an inherited hyperreactive profile of the infants due to viral infection.…”
Section: Infection In Infantsmentioning
confidence: 99%
“…The risk of asthma, recurrent wheeze and long-lasting impairments in lung function following severe RSV-related respiratory illness during infancy is more pronounced among preterm infants with BPD [66,71] and those born at a lower gestational age [68]. Although most studies demonstrating persistent respiratory morbidity following RSV-related respiratory illness have focused on hospitalised infants, a single study has demonstrated persistent airway resistance at 1 year of age in preterm infants following mild RSV infection that did not require hospitalisation [72]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Although it is possible that the immature lungs in preterm infants might be particularly susceptible to long-term damage following severe RSV-related respiratory illness during early life [66,73], RSV infection during such a critical period of lung growth and development can also result in chronic alterations and remodelling of the developing airways independent of pre-existing neonatal factors [50,72]. The underlying mechanisms through which RSV could promote the development of suboptimal lung health and function later in life are yet to be fully elucidated.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 1 more Smart Citation